The anti-Jacobin novel: British conservatism and the French Revolution - Grenby, M O (Cambridge University, 2013)
M. O. Grenby's book offers an insight into the society which produced and consumed anti-Jacobin novels. He examines the strategies used by conservatives in their fiction, thus shedding new light on how the anti-Jacobin campaign was understood and organised in Britain.